Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Rút gọn hả bạn ?
( 3x - 1 )2 - 9( x - 1 )( x + 1 )
= 9x2 - 6x + 1 - 9( x2 - 1 )
= 9x2 - 6x + 1 - 9x2 + 9
= 10 - 6x
( 2x + 3 )( 2x - 3 ) - ( 2x - 1 )2 - ( x - 1 )
= 4x2 - 9 - ( 4x2 - 4x + 1 ) - x + 1
= 4x2 - x - 8 - 4x2 + 4x - 1
= 3x - 9
2( x - 2y )( x + 2y ) + ( x - 2y )2 + ( x + 2y )2
= [ ( x + 2y ) + ( x - 2y ) ]2
= [ x + 2y + x - 2y ]2
= ( 2x )2 = 4x2
\(x^3-3x^2=0\)
\(\Leftrightarrow x^2\left(x-3\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=3\end{matrix}\right.\)
khỉ nghĩ như này..
x3-3x2=0
(=)x2 (x-3)=0
(=)x2=0,hoac x-3=0
(=)x=3
Giải:
a) \(x\left(x-2\right)-\left(x+3\right).x+7+9x=6\)
\(\Leftrightarrow x^2-2x-\left(x^2+3x\right)+7+9x=6\)
\(\Leftrightarrow x^2-2x-x^2-3x+7+9x=6\)
\(\Leftrightarrow4x=-1\)
\(\Leftrightarrow x=-\dfrac{1}{4}\)
Vậy ...
b) \(\left(3x-5\right)\left(7-5x\right)-\left(5x+2\right)\left(2-3x\right)=4\)
\(\Leftrightarrow21x-35-15x^2+25x-\left(10x+2-15x^2+6x\right)=4\)
\(\Leftrightarrow21x-35-15x^2+25x-10x-2+15x^2-6x=4\)
\(\Leftrightarrow30x-37=4\)
\(\Leftrightarrow30x=41\)
\(\Leftrightarrow x=\dfrac{41}{30}\)
Vậy ...
c) \(\left(x+2\right)\left(x^2-2x+4\right)-\left(x^3+3\right)=14x\) (Sửa đề)
\(\Leftrightarrow x^3+8-x^3-3=14x\)
\(\Leftrightarrow5=14x\)
\(\Leftrightarrow x=\dfrac{5}{14}\)
Vậy ...
d) \(\left(x^2-x+1\right)\left(x+1\right)-x^3-3x=2\)
\(\Leftrightarrow x^3+1-x^3-3x=2\)
\(\Leftrightarrow1-3x=2\)
\(\Leftrightarrow-3x=1\)
\(\Leftrightarrow x=-\dfrac{1}{3}\)
Vậy ...
a) \(x\left(x-2\right)-\left(x+3\right)x+7+9x=6\)
=> \(x^2-2x-x-3x+7+9x=6\)
=> \(x^2-2x-x^2-3x+7+9x=6\)
=> \(\left(x^2-x^2\right)+\left(-2x-3x+9x\right)=6-7\)
=> \(4x=-1\)
Vậy \(x=\dfrac{-1}{4}\)
b) \(\left(3x-5\right)\left(7-5x\right)-\left(5x+2\right)\left(2-3x\right)=4\)
=>\(21x-15x^2-35+25x-10x+15x^2-4+6x=4\)
=> \(\left(21x+25x-10x+6x\right)\)\(+\left(-15x^2+15x^2\right)\)\(=4+35+4\)
=> \(42x=43\)
Vậy \(x=\dfrac{43}{42}\)
c) \(\left(x+2\right)\left(x^2-2x+4\right)-\left(x^3+3\right)=14\)
=> \(x^3-2x^2+4x+2x^2-4x+8-x^3-3\)\(=14x\)
=>\(\left(x^3-x^3\right)+\left(-2x^2+2x^x\right)+\left(4x-4x\right)+\left(8-3\right)\)\(=14x\)
=> \(5=14x\)
Vậy \(x=\dfrac{5}{14}\)
d) \(\left(x^2-x+1\right)\left(x+1\right)-x^3-3x=2\)
=> \(x^3+x^2+x+x^2-x+1-x^3-3x=2\)
=>\(\left(x^3-x^3\right)+\left(-x^2+x^2\right)+\left(x-x-3x\right)=2-1\)
=> \(-3x=1\)
Vậy \(x=\dfrac{-1}{3}\)
a, \(\left(x+\frac{4}{3}y^2\right)^2\)
\(=x^2+\frac{8}{3}xy^2+\frac{16}{9}y^4\)
b, \(\left(2x-3y\right)^2\)
\(=4x^2-12xy+9y^2\)
c, \(\left(x^2+2x\right)\left(2x-x^2\right)\)
\(=\left(2x+x^2\right)\left(2x-x^2\right)\)
\(=4x^2-x^4\)
d, \(\left(x+\frac{1}{2}\right)^3\)
\(=x^3+\frac{3}{2}x^2+\frac{3}{4}x+\frac{1}{8}\)
e, \(\left(2x-\frac{6}{5}y\right)^3\)
\(=8x^3-\frac{72}{5}x^2y+\frac{216}{25}xy^2-\frac{216}{125}y^3\)
\(5x\left(x-2y\right)+2\left(2y-x\right)^2=\left(2y-x\right)\left[2\left(2y-x\right)-5x\right]=\left(2y-x\right)\left(4y-7x\right)\)
`(x^3+2y^2)^2`
`=(x^3)^2+2.x^3 .2y^2+(2y^2)^2`
`=x^6+4x^3y^2+4y^4`